Electrochemical deposition of platinum and palladium on gold nanoparticles loaded carbon nanotube support for oxidation reactions in fuel cell - Surin Saipanya (2018)
Pt and Pd sequentially electrodeposited Au nanoparticles loaded carbon nanotube (Au-CNT) was prepared for the electrocatalytic study of methanol, ethanol, and formic acid oxidations. All electrochemical measurements were carried out in a three-electrode cell. A platinum wire and Ag/AgCl were used as auxiliary and reference electrodes, respectively. Suspension of the Au-CNT, phosphate buffer, isopropanol, and Nafion was mixed and dropped on glassy carbon as a working electrode. By sequential deposition method, PdPtPt/Au-CNT, PtPdPd/Au-CNT, and PtPdPt/Au-CNT catalysts were prepared. Cyclic voltammograms (CVs) of those catalysts in 1 M H 2 SO 4 solution showed hydrogen adsorption and hydrogen desorption reactions. CV responses for those three catalysts in methanol, ethanol, and formic acid electrooxidations studied in 2 M CH 3 OH, CH 3 CH 2 OH, and HCOOH in 1 M H 2 SO 4 show characteristic oxidation peaks. The oxidation peaks at anodic scan contribute to those organic substance oxidations while the peaks at cathodic scan are related with the reoxidation of the adsorbed carbonaceous species. Comparing all those three catalysts, it can be found that the PdPtPt/Au-CNT catalyst is good at methanol oxidation; the PtPdPt/Au-CNT effectively enhances ethanol oxidation while the PtPdPd/Au-CNT exceptionally catalyzes formic acid oxidation. Therefore, a different stoichiometry affects the electrochemical active surface area of the catalysts to achieve the catalytic oxidation reactions. © 2014 Surin Saipanya et al.